Pengomposan Sampah Canang dengan Model Pengomposan di Wadah Berbentuk Silinder - Putra, I Made Dwijantara; Setiyo, Yohanes; Sumiyati, Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 8 No 1 (2020): April, 2019)
The use of diameter treatment and supplementary material for cow manure in the process of composting canang waste raw materials can produce quality in accordance with SNI. In this study using three treatments of composting basket diameter: 60 cm in diameter, 40 cm in diameter and 20 cm in diameter with the same height of 100 cm and the addition of cow manure: canang garbage 1: 1. Observed parameters include temperature, pH, carbon and nitrogen compost . The composting process lasts for thirty days with temperatures of 29 - 56 ? and pH of compost 4.3 - 6.9, with the resulting compost color blackish brown. In general, the quality of compost produced from the three treatments with a final C / N ratio of 13.05 - 22.0. Penggunaan diameter perlakuan dan bahan pelengkap kotoran sapi dalam proses pengomposan bahan baku limbah canang dapat menghasilkan kualitas yang sesuai dengan SNI. Dalam penelitian ini menggunakan tiga perlakuan diameter keranjang kompos: diameter 60 cm, diameter 40 cm dan diameter 20 cm dengan tinggi yang sama 100 cm dan penambahan kotoran sapi: sampah canang 1: 1. Parameter yang diamati meliputi suhu, kompos pH, karbon dan nitrogen. Proses pengomposan berlangsung selama tiga puluh hari dengan suhu 29 - 56 ? dan pH kompos 4.3 - 6.9, dengan warna kompos yang dihasilkan berwarna coklat kehitaman. Secara umum, kualitas kompos dihasilkan dari tiga perlakuan dengan rasio C / N akhir 13,05 - 22,0.